Bioconcentration And Translocation Of Heavy Metals In Therapeutic Flora: Ecological And Pharmacological Risks - Arfa Raza*,; Abid Ejaz,; Mahrukh Mumtaz,; Sajida Shabbir,; Niaz Hussain,; Mian Jahan Zaib Rasheed, (Dialogue Social Science Review (DSSR), 2025)
This study investigates the accumulation patterns and health risk implications of four heavy metals such as Zinc (Zn), Iron (Fe), Cadmium (Cd), and Chromium (Cr) present in soil and eight medicinal plant species collected from two distinct locations across multiple sites. Soil and plant samples were analyzed to determine metal concentrations, bioconcentration factors (BCF), and daily intake of metals (DIM). Results showed that Zn levels in soil were within the critical range (1.12-1.70 mg/kg), while plant Zn content varied significantly across species (16.48-25.94 mg/kg), with Adhatoda vasica exhibiting the highest accumulation. Fe concentrations in soil were moderate (10.91-16.04 mg/kg), whereas plant Fe ranged from 12.96 to 23.25 mg/kg, exceeding FAO/WHO limits for edible plants but remaining within therapeutic safety margins. Cd levels in soil (3.45-4.63 mg/kg) exceeded some older permissible limits, yet its uptake by plants remained very low (0.025-0.086 mg/kg), reflecting limited bioavailability. Chromium concentrations in soil (0.028-0.041 mg/kg) were above the critical threshold, with high accumulation in plants (3.40-4.65 mg/kg), surpassing international permissible limits. However, DIM values for all metals were within safe human intake levels. BCFs varied widely among metals and species, with Cr showing the highest accumulation potential. Overall, findings suggest that while the studied soils pose no immediate risk, certain medicinal plants, particularly for Cr and Fe, may require controlled use to avoid chronic exposure. These plants also show potential for use in phytoremediation and bio-monitoring applications. Keywords: Heavy metals, Medicinal plants, Daily Intake of Metal (DIM), Phytoremediation, Soil-plant interaction https://doi.org/10.5281/zenodo.16731396